An In-Depth Analysis of Extending the Duration of General Elections beyond the 90-Day Limit Fixed in the Constitution of the Islamic Republic of Pakistan (1973) - Nawaz, Haq; Bexci, Manual Selvaraj (Pakistan Languages and Humanities Review, 2023)
The study undertakes a nuanced exploration of Pakistan’s constitutional and legal intricacies governing the timing of general elections, employing a multifaceted approach. The objective is to comprehensively analyze key constitutional provisions, including Article 48(5a), 51(5), 153, 219, 222, 224 and 254. Methodologically, a qualitative research design is employed, delving into legal documents, historical records, and scholarly literature. Despite recent amendments to Section 57(1) of the Election Act 2017, granting exclusive authority to the Election Commission of Pakistan (ECP), results reveal persistent debates within the legal community. It emphasizes the supremacy of constitutional principles and recommends invoking the Advisory Jurisdiction of the Supreme Court of Pakistan under constitutional Article 186 to interpret Article 48(5a), 51(5), 153, 219, 222, 224 and 254. Swift legislative reforms are recommended for transparent elections, necessitating a comprehensive legal framework and heightened public awareness. This research underscores the imperative need for legal clarity and reform to fortify Pakistan’s electoral system.